Soil moisture and environmental temperature and humidity sensor-based data Breaches in IoT enable irrigation system design using arduino and FPGA - Yousef A. Baker, El-Ebiary; Somanshu, Choudhary; Keshav, Kumar (2020)
In this work, we have successfully implemented a Moisturization sensor to detect the presence of moisture and trigger pump to on/off depending on the presence of moisture in the soil. The implementation of soil moisture sensor is done on the Arduino board using Yl-69 sensor and the implementation of temperature and humidity is done on Field Programmable Gate Array (FPGA) device. Artix-7 FPGA is used for interfacing the sensor. FPGA devices not only display the temperature value but also makes the whole system power-efficient. We have also surveyed the required water content in soil for the ideal production of crops. We set a threshold level of moisture for every crop if moisture will be less than threshold then pump will automatically start otherwise pump will stop. We have also observed that Sugarcane consumes the maximum amount of water among the list of surveyed crops in Table 1. The minimum amount of water is required by Bean. Therefore, pump up time will greater for sugarcane and minimum for bean